RQ-00201894: A motilin receptor agonist causing long-lasting facilitation of human gastric cholinergically-mediated contractions - John Broad; Nobuyuki Takahashi; Masaomi Tajimi; Masaki Sudo; Adam Góralczyk; Umesh Parampalli; Kesava Mannur; Toshinori Yamamoto; Gareth J. Sanger (Elsevier, 2016)
The aim was to characterise RQ-00201894, a novel non-macrolide motilin agonist, using human recombinant receptors and then investigate its ability to facilitate cholinergic activity in human stomach. A reporter gene assay assessed motilin receptor function. Selectivity of action was determined using a panel of different receptors, ion channels, transporters and enzymes. Cholinergically-mediated muscle contractions were evoked by electrical field stimulation (EFS) of human gastric antrum. The results showed that RQ-00201894, motilin and erythromycin acted as full motilin receptor agonists (EC50: 0.20, 0.11, 69 nM, respectively). In this function, RQ-00201894 had >90-fold selectivity of action over its ability to activate the human ghrelin receptor (EC50 19 nM) and greater selectivity over all other receptors/mechanisms tested. In human stomach RQ-00201894 0.1-30 μM concentration-dependently increased EFS-evoked contractions (up to 1209%; pEC50 6.0). At 0.1-10 μM this activity was usually prolonged. At higher concentrations (3-30 μM) RQ-00201894 also caused a short-lasting muscle contraction, temporally disconnected from the increase in EFS-evoked contractions. RQ-00201894 10 μM did not consistently affect submaximal contractions evoked by carbachol. In conclusion, RQ-00201894 potently and selectively activates the motilin receptor and causes long-lasting facilitation of cholinergic activity in human stomach, an activity thought to correlate with an ability to increase gastric emptying.